Preparation, Characterization, and Photocatalytic Activity of Ni-Cd/Al2O3 Composite Catalyst - Yusmaniar, Yusmaniar; Premono, Agung; Susetyo, Ferry Budhi; Yudanto, Sigit Dwi (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
This study was conducted to determine the effect of the radiation source and radiation time on the methylene blue (MB) solution by adding Ni-Cd/Al2O3 to the percent degradation of MB. To investigate similar purposes, the pH of the MB solution varied as well. The preparation, characterization, and photocatalytic activity of Ni-Cd/Al2O3 are three steps in this research. The Ni-Cd was prepared by mixing Ni(NO3)2.6H2O and Cd(NO3)2.4H2O. Various concentrations of Ni-Cd were mixed with Al2O3, then heated, stirred, dried, and calcined to form Ni-Cd/Al2O3 powder. The dried powder catalysts were characterized using Field emission scanning electron microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDS), Brunauer-emmett-teller (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and Diffused reflectance spectrometer spectra (DR-UV-Vis). Higher degradation was observed at pH 11, when MB was degraded by 68% and 76% using the 5Ni-2Cd/Al2O3 and 6Ni-1Cd/Al2O3 catalysts, respectively. The 6Ni-1Cd/Al2O3 sample has higher absorption, less surface area, and less band gap; therefore, it has higher performance against degraded MB in the solution. In summary, 6Ni-1Cd/Al2O3 is capable of degrading MB and can be utilized in MB dye waste. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).